In Vitro Anthelmintic Activities of Khaya anthotheca and Faidherbia albida Extracts Used in Chad by Traditional Healers for the Treatment of Helminthiasis and In Silico Study of Phytoconstituents - Baigomen Christalin; Masoud Besati; Noumedem Anangmo Christelle Nadia; Mahdi Yaghoobi; Yamssi Cédric; Claire Ciancia; Mounvera Abdel Azizi; Gamago Nkadeu Guy-Armand; Vincent Khan Payne; Haibo Hu (Journal of Tropical Medicine)
Background. Helminthiasis is endemic in Chad and constitutes a public health problem, particularly among school-age children. The aim of this study was to evaluate the anthelmintic activity of extracts of Khaya anthotheca and Faidherbia albida used in Chad by traditional healers for the treatment of helminthiasis. Methods. The anthelmintic activity was assessed against Heligmosomoides polygyrus and Caenorhabditis elegans larvae using the Worm Microtracker. Embryonated eggs, L1, L2, and L3 larvae of H. polygyrus were obtained after 24 h, 48 h, and 7 days of coproculture and L4 larvae of C. elegans culture using standard procedures. One hundred microliters of extracts at various concentrations, with albendazole and distilled water were, put in contact with 100 µL of H. polygyrus suspension (containing 50 parasites at various developmental stages) in a microplate and incubated for 20 h at 25°C in the Worm Microtracker. The same procedure was adopted for C. elegans, but with 180 µL of OP50. 19 µL of C. elegans suspension (containing 50 larvae) was put in contact with 1 µL of extract at various concentrations and incubated in the Worm Microtracker. Docking studies were carried out using the Schrodinger Maestro software’s Glide module. The score function in the software was used to rank and group distinct possible adduct structures generated by molecular docking. Results. The aqueous and ethanolic extracts of F. albida at a concentration of 2.5 mg/mL showed the same activity as albendazole (100 ± 0.00) on hatching. The IC50s of the aqueous extracts of the two plants (IC50: 0.6212 mg/mL and 0.71 mg/mL, respectively) were comparable on egg hatching of H. polygyrus with no significant difference (p≥0.05) with respect to the ethanol extracts (IC50: 0.70 mg/mL and 0.81 mg/mL, respectively). There was no significant difference between the percentage inhibition of extracts and albendazole on the L1 larvae of H. polygyrus (p≥0.05). The aqueous extracts acted more effectively than the ethanol extracts on the L1 larvae of H. polygyrus with an IC50 of 0.5588 and ∼9.858e − 005 mg/ml, respectively, for K. anthotheca and F. albida. The aqueous extracts of K. anthotheca and F. albida on L3 larvae of H. polygyrus had inhibitory percentages of 92.6 ± 0.62 and 91.37 ± 0.8 at 2.5 mg/mL which were lower than albendazole (100 ± 0.00). The aqueous extracts of K. anthotheca and F. albida on C. elegance showed IC50 of 0.2775 µg/mL and 0.5115 µg/mL, respectively, and were more effective than the ethanol extracts. Examining K. anthotheca and F. albida through the interaction with the protein receptor and its results also confirmed our assumption that the compound used has hydroxyl and carbonyl groups as well as aromatic rings and is exposed to phenolic and flavonoid groups in a more specific way, and it shows a better inhibitory effect. Conclusions. This study scientifically validates the use of extracts of the two plants in the traditional treatment of helminthiasis. However, it will be necessary to evaluate the in vivo anthelmintic activity and toxicity. Examining the ADME properties of these compounds also supports the potential of these ligands to be transformed into pharmaceutical forms.